Effects of Balneotherapy and Physical Therapy on Sleep Quality in Patients with Osteoarthritis Aged 50 to 85 Years - Erkan KAYA,; Cengiz KAPLAN,; Alparslan Bayram ÇARLI,; Ümit GÜZELKÜÇÜK, (Archives of Rheumatology, 2016)
Objectives: This study aims to investigate the effect of balneotherapy (BT) and physical therapy (PT) on sleep quality in patients with knee osteoarthritis (OA) aged 50 to 85 years. Patients and methods: A total of 199 patients (76 males, 123 females; mean age 67.8±7.3 years; range 50 to 85 years) suffering from knee OA (Kellgren-Lawrence grade 2-3) for more than six months were enrolled. Sleep and functional status were assessed at baseline and after 19 sessions of BT and 15 sessions of PT by using Pittsburgh Sleep Quality Index and Western Ontario and McMaster Universities Osteoarthritis Index, respectively. Results: A high prevalence of abnormal sleep quality in patients with knee OA was observed. The most common abnormality was sleep fragmentation (71%), with an increased sleep disturbance score. Patients reported significantly improved sleep, pain, stiffness, and functional status after BT and PT. Conclusion: Balneotherapy and PT improved self-reported sleep and functional status in patients with OA aged 50 to 85 years. We may conclude that BT and PT, which are used in the treatment of OA, not only reduce nocturnal pain, but also improve sleep quality.